Frequency of Gall Stones Among Patients With Helicobacter pylori Gastritis Presenting at a Tertiary Care Hospital - Nawaz, Muhammad; Haque, Anwar Ul (Biological and Clinical Sciences Research Journal, 2025)
Helicobacter pylori infection is a common gastrointestinal condition and has been implicated in various hepatobiliary disorders. Emerging evidence suggests a possible association between H. pylori gastritis and gallstone disease. Objective: To determine the frequency of gallstones among patients with Helicobacter pylori gastritis presenting at a tertiary care hospital. Methods: This study was conducted in 82 patients with H. pylori gastritis, diagnosed based on clinical symptoms and histopathological examination. Patients were assessed for the presence of gallstones. Diagnosis of gallstones was confirmed using abdominal ultrasonography based on reflective anterior echo, mobility, and posterior acoustic shadowing. SPSS 25 was used for data analysis. The chi-square test was used to stratify gallstones by demographics and comorbidities. A p-value ≤ 0.05 was considered significant. Results: The Mean age of the cohort in this study was 51.71 ± 15.21 years. Female patients were the majority, at 57.3%. Gallstones were observed in 31.7% of patients with H. pylori gastritis (n=26). A significant association was found between female gender and gallstones (P < 0.001). No statistically significant associations between gallstones and demographics or comorbidities were observed. Conclusion: A considerable proportion of patients with Helicobacter pylori gastritis had gallstones, 31.7% in the present study. Gallstones were associated with female gender, and a high proportion of patients with higher BMI had gallstones.